Gendered organizations and their effects on VAWS handling the cases of Cebu City's bantay banay and collocated Philippine National Police women and children's desk. - Librado, Reyanne Joy P (2016.)
The enactment of the Anti-Violence Against Women and Children (VAWC) Act in 2004 changed the dynamics of perceiving Violence Against Women from being a ?private family affair?, to a ?public crime?. Civil societies, Local Government Units (LGUs) and the Philippine National Police Women and Children Protection Desk (WCPD) are the primary institutions that ensures this reorientation in combating and handling VAWC victims. At the advent of the shift of perception within the law, we wanted to examine handling of VAWC through two cases of varying degrees of organizational cultures: the PNP WCPD and the Bantay Banay. Our research attempts to examine the effects of the varying degrees of genderedness of organizations in responding to Violence Against Women and Children, using the cases of the Bantay Banay model of the Lihok Pilipina Foundation with the PNP Women and Children?s Desk of Cebu City. Our study looked closely at their respective gendered organizational behaviour in three primary aspects namely, (1) depth of Gender and Development integration (2) VAWC handling and (3) genderedness of organizations affecting VAWC. GAD integration and VAWC handling were examined through a mixed method of quantitative and qualitative assessments. The study found out that generally, that while both organizations have efforts to integrate GAD in their processes, the women?s organization has greater volumes of training on gender sensitivity that sees Anti-VAWC a an advocacy. In contrast, women police officers have special courses, directed by the legal implementation of the RA 9262. The depth of the integration of gender values is relative to the manner and degree of taking sustained gender-related initiatives. Seeing VAWC handling through women?s everyday lived experience highlights the multiplicity of experiences that reaffirms the gendered processes of organizations. It debunks the dominant claim that organizations are neutral since handling of VAWC (as praxis) is affected by people?s personal beliefs on gender. The orientations of handling VAWC are indeed affected by the different gendered organizational cultures of the PNP WCPD and the Bantay Banay, which uniquely fulfils specifics functions that contributes to the effectivity of handling VAWC. We could appreciate, that regardless of positionality, women personnels of these different organizations share the effects of handling VAWC in their personal lives through experiential re-education in transforming their own relationships. Therefore, the particularity of the personal effect of exposure to VAWC, opens the potential of mainstreaming gender fair cultures into organizations and its personnel.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Anti-Violence Against Women; Violence Against Women